Diseño de estrategias de promoción turística basada en herramientas web para el cantón La Maná. - Patango Ayala, Norma Rocio (2024)
The objective of this project is to design tourism promotion strategies based on web tools for the dissemination of tourist places in La Maná Canton, Cotopaxi Province. The identified problem inside the research is the possible lack of a website to promote the places, services, festivities, and other tourist attractions in the sector. A methodology with a mixed approach of documentary type, field with interview, survey and direct observation was used as an information collection technique. A sample of 16 tourism service providers and 92 tourists from La Maná canton is estimated. As a result, according to providers, local authorities show little interest and they do not provide support for the tourism development of La Maná canton which hinders its tourism potential and limits growth opportunities for local businesses. In addition, based on the application of the research instrument, it was obtained that 100% of the tourists surveyed revealed the need of having a website that provides tourist information about the canton. According to this, the designed website has sections on home, history, tourist attractions, cultural attractions, spas, cultural festivals, businesses, lodging services, restaurants, and emergency services. It was concluded that the website improves accessibility to information on different tourist attractions in the canton, so that visitors can find easily the information they need.